The Relationship Between Merchants Knowledge and Attitude Toward the Obedience of Mask Use in Preventing Covid-19 - Aulia; Titik Sumiatin; Su’udi Su’udi (International Journal of Advanced Health Science and Technology, 2022)
The COVID-19 outbreak began in December 2019. In preventing its transmission, society across the world agrees to use a mask for their safety. However, today, people, primarily some merchants who sell their stuff around the tourism places, still do not obey the regulation to wear a mask. Hence, this study aims to know the relationship between merchant knowledge and attitude toward the obedience of using a mask in preventing the COVID-19 transmission at the religious tourism of Sunan Bonang Tuban. The research design used in this study is the correlation analysis that uses a cross-sectional approach. Moreover, the sampling technique used in this study is Simple Random Sampling with 105 populations and 83 samples of merchants. The data technique used in this study is a questionnaire. Then, the researcher analyzes the questionnaire with a percentage and does a crosstab by using the Spearman Rank Correlation test. The finding of this study presents that most of the merchants at religious tourism of Sunan Bonang Tuban have good knowledge in preventing COVID-19 transmission. It is about Forty-nine people (59,0%). Then, fifty people (60,2%) have a positive attitude. Moreover, the finding presents that almost half of the merchants, thirty-five people (42,2%), obey the regulation to wear the mask. The result of Spearman Rank Correlation test is α =0.00 < 0.05. This result shows the relationship between knowledge and obedience in using the mask. The result of the test is α =0.00 < 0.001 shows there is a relationship between the attitude and the obedience in using the mask of merchants to prevent COVID-19 at the religious tourism of Sunan Bonang Tuban. The knowledge and attitude of merchants influence their obedience in using the mask. It means that the more increased merchants' knowledge and attitude, the more increased merchant obedience. In increasing and encouraging other merchants' knowledge and attitude, the government must have a good strategy. One of the appropriate strategies is doing counseling of using a mask to prevent COVID-19 transmission.